2014
DOI: 10.1103/physrevlett.113.187202
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall Effect in Weyl Metals

Abstract: We present a theory of the anomalous Hall effect (AHE) in a doped Weyl semimetal, or Weyl metal, including both intrinsic and extrinsic (impurity scattering) contributions. We demonstrate that a Weyl metal is distinguished from an ordinary ferromagnetic metal by the absence of the extrinsic and the Fermi surface part of the intrinsic contributions to the AHE, as long as the Fermi energy is sufficiently close to the Weyl nodes. The AHE in a Weyl metal is thus shown to be a purely intrinsic, universal property, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
447
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 452 publications
(472 citation statements)
references
References 27 publications
12
447
1
Order By: Relevance
“…For k 0 = 0, the two Weyl points collapse onto each other giving rise to a topologically trivial (i.e with a zero Berry curvature flux) massless degenerate Dirac fermion. The topological nature of a WSM leads to a host of interesting physics, for example Berry curvature induced anomalous transport, namely charge and thermal Hall conductivities [43][44][45][46][47][48] and open Fermi arcs on surfaces 11,[49][50][51][52][53][54][55] . Anomalous transport phenomena, however, have been already known to exist in a variety of systems which possess a non-trivial distribution of the Berry curvature flux 56,57 .…”
Section: Introductionmentioning
confidence: 99%
“…For k 0 = 0, the two Weyl points collapse onto each other giving rise to a topologically trivial (i.e with a zero Berry curvature flux) massless degenerate Dirac fermion. The topological nature of a WSM leads to a host of interesting physics, for example Berry curvature induced anomalous transport, namely charge and thermal Hall conductivities [43][44][45][46][47][48] and open Fermi arcs on surfaces 11,[49][50][51][52][53][54][55] . Anomalous transport phenomena, however, have been already known to exist in a variety of systems which possess a non-trivial distribution of the Berry curvature flux 56,57 .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, each nontrivial slice contributes an e 2 /h to the Hall conductivity [9-11] producing σ xy = be 2 /πh in the bulk, and also contributes one edge state to the surface forming a surface Fermi arc connecting the two projected Weyl points. Recently, the Weyl points and surface arcs appear to be observed in optical experiments [23][24][25].This progress may herald a flurry of exciting experiments on the appealing transport effects [26][27][28] predicted in WSM, e.g., the chiral magnetic effect [29][30][31][32][33][34][35][36] when b 0 becomes nontrivial in the absence of P symmetry, and the axial magnetic effect [37,38] when τ b, viewed as a gauge field coupling oppositely to the left-and right-handed Weyl fermions, varies spatially.Here we discover a universal effect in lightly-doped WSMs, by examining the semiclassical dynamics of Weyl quasiparticles in the ballistic regime. The presence of Weyl points leads to substantial Berry curvatures.…”
mentioning
confidence: 99%
“…This progress may herald a flurry of exciting experiments on the appealing transport effects [26][27][28] predicted in WSM, e.g., the chiral magnetic effect [29][30][31][32][33][34][35][36] when b 0 becomes nontrivial in the absence of P symmetry, and the axial magnetic effect [37,38] when τ b, viewed as a gauge field coupling oppositely to the left-and right-handed Weyl fermions, varies spatially.…”
mentioning
confidence: 99%
“…WSM materials such as the TaAs-family pnictides [7,8] and MoTe 2 [9,10] have recently been discovered primarily by observation of the unique Fermi arcs of surface states through angle-resolved photoemission spectroscopy [11][12][13][14][15][16]. Because Weyl points are monopole sources or drains of the Berry curvature of Bloch wave functions in momentum space, a WSM can exhibit an anomalous Hall effect when breaking the time-reversal symmetry (TRS) [17][18][19] or a spin Hall effect [20], as a linear response to an external electric field. Recent theoretical [21][22][23][24][25][26][27][28][29][30] and experimental [31][32][33][34] studies have revealed giant nonlinear optical responses in inversion-symmetry-breaking WSMs, such as the photocurrent from the circular photogalvanic effect (CPGE), second harmonic generation (SHG), and nonlinear Hall effect.…”
mentioning
confidence: 99%